Do Laws Carry History? A Study of Abortion in the Indian Subcontinent - Sahgal, Ami; Aggarwal, Anisha; Manning, Vinoj (Advances in Social Sciences Research Journal, 2026)
This paper examines whether contemporary abortion law and discourse in India carry traces of earlier frameworks governing reproduction in the Indian subcontinent. Drawing on religious, legal, and medical texts from the Vedic period onwards, alongside colonial legislation, parliamentary debates surrounding the Medical Termination of Pregnancy (MTP) Act and its 2021 amendment, and insights from reproductive health practice, the paper traces changing approaches to abortion across time. It argues that while authority over abortion shifted from religious and normative traditions to colonial criminal law and later to medical regulation, enduring concerns around lineage, legitimacy, morality, and social order continue to shape abortion discourse. The paper finds that legal reform has expanded access and adopted more inclusive language, yet abortion remains framed as a conditional and regulated exception rather than an autonomous right. Contemporary abortion law thus reflects not a clean break from the past but a layered inheritance of historical ideas and institutions.